Analisis Pola Kemitraan Petani Penangkar Dengan PT. Sang Hyang Seri (persero) Unit Produksi Benih I Sidrap - ainun muthmainnah; Nurhapsa Nurhapsa; Arman Arman (Jurnal Agribis, 2023)
This research is entitled analysis of partnership patterns of breeder farmers with PT. Sang Hyang Seri (Persero) Sidrap Seed Production Unit. This study analyzes the partnership pattern of breeder farmers with PT. Sang Hyang Seri (Persero) Sidrap Seed Production Unit. The form of data collection in this study is primary data and secondary data. By using the method of descriptive data analysis by simply tabulating, the data obtained from the sample either by interview or by existing questionnaires. The results of this study indicate that the partnership pattern that exists between breeder farmers and PT. Sang Hyang Seri (Persero) Sidrap Seed Production Unit is included in the ENOUGHLY EFFECTIVE category. From the results of the interviews conducted, it was found that the partnership pattern used was an agribusiness operational cooperation partnership (KOA) pattern. In the partnership implementation process, there are 7 activities carried out, namely: location survey, partnership proposal, administration and partnership contract, implementation/monitoring, evaluation and operational assistance. While the effectiveness of the partnership pattern that has been established is quite effective, however there are several factors that need to be further improved, namely the supply of heavy equipment and the availability of means of transporting captive-bred animals.